Analisis Semiotika Komunikasi Budaya: Perspektif Bugis Dalam Film Tenggelamnya Kapal Van Der Wijck - Anitha Nurchalisah Thaha; Fian Bin Mus; Muh Haykal Saputra (Harmoni: Jurnal Ilmu Komunikasi dan Sosial, 2024)
The film "Tenggelamnya Kapal Van Der Wijck" (TKVDW) depicts a tragic intercultural romance and represents the richness of Bugis culture woven into its narrative. This research aims to analyze the representation of Bugis culture in the film through a semiotic approach. Bugis cultural symbols, both visual and verbal, are identified and interpreted in intercultural communication. The results show that the film successfully presents Bugis cultural symbols rich in meaning, ranging from traditional clothing, language, to values such as siri' (self-esteem) and lempu' (leadership). These symbols are not only markers of identity but also play a role in intercultural communication as a bridge and a source of conflict. The representation of Bugis culture in the film also shows the power dynamics between Bugis, Minangkabau, and Dutch cultures during the colonial era. This research is expected to contribute to cultural and communication studies, especially in understanding the representation of Bugis culture in popular media.